A holistic IT infrastructure management framework. (11th February 2020) - Varga, Sergio; Barreto, Gilmar; Battaglin, Paulo David
Information systems (IS) are becoming increasingly complex and they have issues to be solved. New technologies, products and deployment models make the management of an IS difficult to maintain. Organisations need to deploy tools, processes, and governance in their information technology (IT) environment to support their IS. This increases even more the complexity of an IT environment and it drives organisations to manage the environment by silos or components. This type of management inhibits organisations to ensure the entire environment has been properly managed according to what was agreed in the outsourcing contract despite the usage of IT frameworks available. This paper intends to analyse and identify these issues, and also to propose an IT management framework that will help organisations to provide an efficient service. This service is based on agreed scope and will ensure that all contracted services will be deployed with accuracy, completeness, management, and awareness.